2010
DOI: 10.4314/ajns.v27i2.55090
|View full text |Cite
|
Sign up to set email alerts
|

Strokes among youth ( 15 to 45 years old) in the neurological department of the medical teaching hospital, campus-lome

Abstract: Mots clés : Accident vasculaire cérébral (AVC), accident vasculaire cérébral, pays en développement, sujets jeunes, Togo Key words : Stroke, youth, developing country, Togo RESUME Introduction En Afrique subsaharienne les accidents vasculaires cérébraux (AVC) représentent la troisième cause de mortalité et la première cause d'incapacité motrice dans les grands centres de neurologie. Ils surviennent souvent chez des sujets de plus de 50 ans. L'OMS a noté que le nombre de décès chez les adultes jeunes (15-45 ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 4 publications
5
6
1
Order By: Relevance
“…In a study done in urban population in Saint-Louis of Senegal [21], 13% of hypertension is found between 15 and 24 years; 23% of HTA between 25 and 34 years; 33% HTA between 35 and 44 years and 58% for those aged 45 to 54 years. This very high rate of hypertension at 80.4% is in agreement with the studies of Balogou [3] in Togo and Kalita [13] in India, which found respectively an HTA rate of 79.9% and 79%. In the Black American study by Love B.…”
Section: Etiologies Of Hemorrhagic Strokesupporting
confidence: 92%
See 3 more Smart Citations
“…In a study done in urban population in Saint-Louis of Senegal [21], 13% of hypertension is found between 15 and 24 years; 23% of HTA between 25 and 34 years; 33% HTA between 35 and 44 years and 58% for those aged 45 to 54 years. This very high rate of hypertension at 80.4% is in agreement with the studies of Balogou [3] in Togo and Kalita [13] in India, which found respectively an HTA rate of 79.9% and 79%. In the Black American study by Love B.…”
Section: Etiologies Of Hemorrhagic Strokesupporting
confidence: 92%
“…The average age in our series was 39.95 years old. This is relatively close to that of Balogou which was 38.5 years old [3]. In another study, the average age was smaller: 33 years for the study of Mohamed Chraa [6].…”
Section: Epidemiological Datasupporting
confidence: 71%
See 2 more Smart Citations
“…[1] The thalamus is a diencephalic structure whose nuclei represent a gateway for input and output to and from the cerebral cortex. The thalamus is supplied by four arterial branches, (thalamoperforating, thalamogeniculate, thalamotuberal and posterior choroidal arteries).…”
Section: Introductionmentioning
confidence: 99%